Voltammetric behaviour of a modified electrode with azide copper octa(3-aminopropyl)octasilsesquioxane composite in the oxidation of ascorbic acid - Carmo, Devaney Ribeiro do [UNESP]; Paim, Leonardo Lataro [UNESP]; Silvestrini, Daniela Rodrigues [UNESP]; Sá, Acelino Cardoso de [UNESP]; Bicalho, Urquisa de Oliveira [UNESP]; Stradiotto, Nelson Ramos [UNESP] (My University, 2011)
A novel nanostructured composite, azide copper octa (3-aminopropyl)octasilsesquioxane (ASCA) was incorporated into a graphite paste electrode and the electrochemical studies were conducted with cyclic voltammetry. The cyclic voltammogram of the modified graphite paste electrode with ASCA (GPE-ASCA), showed one redox couple with formal potential (E  ) = 0.30 V and an irreversible process at 1.1 V (vs Ag/AgCl; NaCl 1.0 mol L-1 ; v = 20 mV s-1 ). The redox couple with (E  ) = 0.30V presents an electrocatalytic response for determination of ascorbic acid. The modified electrode gives a linear range from 1.010-4 – 1.010-3 mol L-1 (r = 0.998) for the determination of ascorbic acid with detection limit of 6.910-5 mol L-1 and standard deviation of 2.3% for n = 3 . The amperometric sensitivity was 122.1 mA/mol L-1 for ascorbic acid. The application this electrode was tested and ascorbic acid in three commercial pharmaceutical product (Cebion, Cewin and Redoxon) have been determined.
Keywords: Silsesquioxane; ascorbic acid; graphite paste electrode; voltammetry; modified electrode